Business Research An Illustrative Guide to Practical Methodological Applications in Selected Case Studies - Buys, Pieter W.; Oberholzer, Merwe (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book focuses on research methodologies that apply to business research, particularly for researchers and managers embarking thereon to support managerial decision-making in the industry. In doing so, the book's objective is to guide business researchers in identifying, defining, and applying rigorous academic methodologies that will enable them to formulate, design, and execute effective research that answers their specific management problems. Such guidance can empower organizational managers to understand that business research can contribute to practical solutions to actual problems experienced in the industry. In addition, by emphasizing the integrative nature between (1) academic research and (2) experienced industry problems, it becomes possible to foster an awareness of such research's potential impact on organizational performance management, sustainability, and resilience. With that, attention is given to narrowing the gap between theory and practice, which requires that fundamentals of scientific research be adhered to while maintaining the delicate balance between a practice-friendly guide to pragmatically sound and academically rigorous business research. Pieter W. Buys is Professor in the Accounting Sciences at the North-West University, South Africa, and is currently the Research Director of the Management Cybernetics research entity within the Faculty of Economic and Management Sciences. His academic qualifications include Masters' degrees in Managerial Accounting (M.Com), Industrial Engineering (M.Eng) and Business Administration (MBA). He also holds two PhDs; Managerial Accounting and Accounting Philosophy. His research focuses primarily on applied corporate management from a business systems perspective. Before his appointment, he occupied senior management positions in various corporates as well as project management positions at a Big 4 audit firm and ERP consulting firm in Canada and South Africa. Merwe Oberholzer is Professor in the Accounting Sciences at the North-West University, South Africa, and is currently employed in the Management Cybernetics research entity within the Faculty of Economic and Management Sciences. His academic qualifications include a Masters' degree in Managerial Accounting (M.Com), and he holds a Ph.D. in Managerial Accounting. He has taught Management Accounting and Financial Management in the Chartered Accountancy and Chartered Management Accountancy programs extensively.
Chapter 1: Introduction,- Chapter 2: A roadmap to business research -- Chapter 3: The effect of the adoption of International Financial Reporting Standards on foreign portfolio investment in Africa -- Chapter 4: Determining the impact of different forms of stationarity on financial time series analysis -- Chapter 5: Measuring the relationship between intraday returns, volatility spill-overs and market beta during financial distress -- Chapter 6: The Relationship between the Forward and the Realized Spot Exchange Rate in South Africa -- Chapter 7: Policy implementation of credit management at selected South African universities of technology -- Chapter 8: Analyzing white maize hedging strategies in South Africa Frans Dreyer, André Heymans & Chris van Heerden -- Chapter 9: Developing a water disclosure index: An integrative perspective -- Chapter 10: Perceptions of school management teams on the influence of instructional leadership on accounting learner performance in secondary schools -- Chapter 11: Using interpretive phenomenology to understand the tax compliance lived experiences of small business owners -- Chapter 12: Utilizing an in-depth qualitative approach in a non-Western context: Exploring the demands and resources of first-year students from the perspectives of support structures at a peri-urban university campus -- Chapter 13: The legitimacy predicament of current-day accounting theory -- Chapter 14: A Case Study Approach To Develop A Competitive Strategy For A Selected Automotive Distribution Company In Preparation For Saudi Vision 2030 -- Chapter 15: A Risk-Based Approach To The Acquisition Of Electronic Mine Safety Equipment -- Chapter 16: Developing A Channeling Framework For Healthcare Service Provider Networks For A Medical Scheme In South Africa -- Chapter 17: Synthesis And Evaluation Of Engineering Processes For The Development Of Airborne Electronic Equipment -- Chapter 18: The Development Of A Growth-Strategy Support Model To Enable Cross-Border Expansion Stratagems -- Chapter 19: Concluding Comments. .
Keywords: Operations research; Executives -- Training of; Operations Research and Decision Theory; Management Education